Antioxidant and DNA Repair Stimulating Effect of Extracts from Transformed and Normal Roots of Rhaponticum carthamoides against Induced Oxidative Stress and DNA Damage in CHO Cells. (29th February 2016) - Skała, Ewa; Sitarek, Przemysław; Różalski, Marek; Krajewska, Urszula; Szemraj, Janusz; Wysokińska, Halina; Śliwiński, Tomasz
Abstract : Rhaponticum carthamoides has a long tradition of use in Siberian folk medicine. The roots and rhizomes of this species are used in various dietary supplements or nutraceutical preparations to increase energy level or eliminate physical weakness. This is the first report to reveal the protective and DNA repair stimulating abilities of R. carthamoides root extracts in Chinese hamster ovary (CHO) cells exposed to an oxidative agent. Both transformed root extract (TR extract) and extract of soil-grown plant roots (NR extract) may be responsible for stimulating CHO cells to repair oxidatively induced DNA damage, but CHO cells stimulated with extract from the transformed roots demonstrated significantly stronger properties than cells treated with the soil-grown plant root extract. These differences in biological activity may be attributed to the differences in the content of phenolic compounds in these root extracts. Preincubation of the CHO cells with TR and NR extracts showed an increase in gene expression and protein levels of catalase ( CAT ) and superoxide dismutase ( SOD2) . R. carthamoides may possess antioxidant properties that protect CHO cells against oxidative stress.